If I Could Turn My Tongue Like That : The Creole Language of Pointe Coupee Parish, Louisiana - Klingler, Thomas A. (Book collections on Project MUSE., 2003)
If I Could Turn My Tongue Like That, by Thomas Klingler, is an in-depth study of the Creole language spoken in Pointe Coupee Parish, Louisiana, a community situated on the west bank of the Mississippi River above Baton Rouge that dates back to the early eighteenth century. The first comprehensive grammatical description of this particular variety of Louisiana Creole, Klingler's work is timely indeed, since most Creole speakers in the Pointe Coupee area are over sixty-five and the language is not being passed on to younger generations. It preserves and explains an important yet little unders.